A novel role of the miR‐152‐3p/ERRFI1/STAT3 pathway modulates the apoptosis and inflammatory response after acute kidney injury. Issue 9 (25th June 2020) - Ma, Piyong; Zhang, Chunmei; Huo, Pengfei; Li, Yan; Yang, Hailing
Abstract: Acute kidney injury (AKI) is one of the most common and serious complications in the development of sepsis. Many microRNAs are closely related to the occurrence, development, and prognosis of sepsis AKI (but the effect and mechanism of miR‐152‐3p in it is unclear). Meanwhile, the ERBB receptor feedback inhibitor 1 (ERRFI1) has a negative regulatory effect on signal transducer and activator of transcription 3 (STAT3) phosphorylation on uterine epithelial cells. But, the relationship between miR‐152‐3p and renal function, inflammatory factors, prognosis in AKI, and the mechanism is not clear. Analyzing sepsis‐induced AKI rats and the cell model, our results revealed that miR‐152‐3p was upregulated in septic AKI patients and positively correlated with serum creatinine, urea nitrogen, interleukin 1β (IL‐1β) and tumor necrosis factor α (TNF‐α). Downregulation of miR‐152‐3p with the inhibitor could dramatically attenuate caspase‐3, bromodeoxyuridine and IL‐1β, and TNF‐α in the AKI rats' model. Furthermore, downregulation of miR‐152‐3p attenuated lipopolysaccharide‐induced apoptosis and inflammatory response in HK‐2 and HEK293 cells. To further explore the mechanisms, we found ERRFI1 was appreciably downregulated and STAT3 was upregulated in AKI, whereas ERRFI1 was radically upregulated and STAT3 was greatly downregulated after the addition of miR‐152‐3p inhibitor, no matter in vivo or in vitro. Summarily, our study confirmed that miR‐152‐3p could promote the expression of STAT3 by targeting ERRFI1, aggravate cell apoptosis and inflammatory response, and thereby aggravate kidney injury in sepsis AKI.